The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s1413-86702008000300007
|View full text |Cite
|
Sign up to set email alerts
|

Indications of a new antibiotic in clinical practice: results of the tigecycline initial use registry

Abstract: Tigecycline is the first of a new class of antibiotics named glycylcyclines and it was approved for the treatment of complicated intra-abdominal infections and complicated skin and skin structure infections. Notwithstanding this, tigecycline's pharmacological and microbiological profile which includes multidrug-resistant pathogens encourages physicians' use of the drug in other infections. We analyzed, during the first months after its launch, the tigecycline prescriptions for 113 patients in 12 institutions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 14 publications
(14 reference statements)
2
14
0
1
Order By: Relevance
“…Similarly in Argentina, 78% of the tigecycline prescriptions were for off-label use during its first month of commercial use, especially for VAP (61%) due to MDR Acinetobacter spp infection. 14 In our study, cases with HAP were older (mean age 78 years), were more frequently admitted to the intensive care unit (76.3%), and had higher SOFA score (mean 8.6). Prior antibiotic use was found in almost all cases.…”
Section: Discussionmentioning
confidence: 54%
“…Similarly in Argentina, 78% of the tigecycline prescriptions were for off-label use during its first month of commercial use, especially for VAP (61%) due to MDR Acinetobacter spp infection. 14 In our study, cases with HAP were older (mean age 78 years), were more frequently admitted to the intensive care unit (76.3%), and had higher SOFA score (mean 8.6). Prior antibiotic use was found in almost all cases.…”
Section: Discussionmentioning
confidence: 54%
“…Currently, tigecycline is FDA approved for complicated intraabdominal infections (cIAI) and complicated skin-skin structure infections (15). With high susceptibilities demonstrated in surveillance studies (2) and positive clinical outcomes shown in trial data from subpopulations infected with ESBL-producing Enterobacteriaceae (6,23), tigecycline has been increasingly utilized as a treatment option. Given these occurrences and the few available studies describing the exposure-response relationship for the treatment of gram-negative organisms (15,19,21), it seems reasonable to uncover the pharmacodynamics of tigecycline.…”
mentioning
confidence: 99%
“…Four studies including 118 patients with infections caused by ESBLproducing enterobacteria provided some additional data. [244][245][246][247] The most frequent infections were cIAI, cSSTI and HAP. Clinical response rates ranged between 63% and 81%, but the percentage of patients receiving combination therapy was not always specified.…”
Section: When and How Should Fosfomycin Be Used In The Treatment Of Imentioning
confidence: 99%